2010
DOI: 10.1111/j.1863-2378.2009.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominance and Persistence of a Single Clone of Listeria ivanovii in a Manchego Cheese Factory Over 6 Months

Abstract: In an attempt to study the diversity and persistence of molecular subtypes of pathogenic Listeria spp. in a cheese factory at the La Mancha region of Spain, 43 samples were taken from incoming raw milk (cow's, ewe's, goat's and mixed species) and from certain food-contact and environmental surfaces before and/or after sanitation. Of these samples, 12 contained pathogenic Listeria. From the chromogenic agar plates corresponding to those, 46 phosphatidylinositol-specific phospholipase C-positive isolates were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Thus, strains with increased resistance to sanitizers, higher adaptability to stress, or better ability to form biofilms might be better suited to persist in inhospitable environments such as those prevailing in food industries. Persistence of L. ivanovii in food processing environments has been also previously reported by Vázquez-Villanueva et al [ 15 ] who identified a persistent L. ivanovii subsp. ivanovii pulsotype from ewe's and goat's raw milk samples from asymptomatic animals at farm level and from swabs obtained from the inner surfaces of raw milk truck tanks and the milk dump tank at the cheese factory level.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, strains with increased resistance to sanitizers, higher adaptability to stress, or better ability to form biofilms might be better suited to persist in inhospitable environments such as those prevailing in food industries. Persistence of L. ivanovii in food processing environments has been also previously reported by Vázquez-Villanueva et al [ 15 ] who identified a persistent L. ivanovii subsp. ivanovii pulsotype from ewe's and goat's raw milk samples from asymptomatic animals at farm level and from swabs obtained from the inner surfaces of raw milk truck tanks and the milk dump tank at the cheese factory level.…”
Section: Discussionsupporting
confidence: 78%
“…A similar phenomenon could also occur for other members of the genus Listeria , including L. ivanovii . In fact, a study by Vázquez-Villanueva et al [ 15 ] has provided evidence for the persistence of a L. ivanovii subsp. ivanovii isolate in a Spanish cheese factory.…”
Section: Introductionmentioning
confidence: 99%
“…Listeria monocytogenes from dairy farm to raw food Latorre et al (2011) presented evidence that a source of L. monocytogenes contamination was milking equipment, since 67.6% of in-line milk filter samples and 19.7% of bulk tank milk samples were positive for L. monocytogenes. Predominant and persistent strains of Listeria might be more adapted to the specific ecological environment of the milking system than strains that appear only sporadically (Vazquez-Villanueva et al, 2010;Latorre et al, 2011).…”
Section: Raw Milkmentioning
confidence: 99%
“…Some specific subtypes of L. monocytogenes can also persist for extended periods in many different food processing environments , including dairy food processing plants (Vazquez-Villanueva et al, 2010;Latorre et al, 2011). In the dairy plant, Listeria can persist in a variety of sites, although it is most frequently found in moist environments or areas with condensed or standing water or milk, including drains, floors, coolers, conveyors and case washing areas (Arimi et al, 1997;Ho et al, 2007b;Fox et al, 2009).…”
Section: Processing Environmentmentioning
confidence: 99%
“…Potential sources of Listeria spp. in cheese, apart from the raw material (i.e., the milk), also include the environment of the processing plants [ 71 , 72 ]. Given the low rate of isolation of the pathogens in raw milk, close monitoring of cheese production plants is necessary to prevent contamination by the bacteria.…”
Section: Discussionmentioning
confidence: 99%